AKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK BUAH MAHKOTA DEWA (Phaleria macrocarpa) DENGAN EKSTRAK HERBA MENIRAN HIJAU (Phyllantus niruri Linn.) TERHADAP PERTUMBUHAN Staphylococcus aureus - Aulia Rahmah Triastanti; Putri Vidiasari Darsono; Siti Malahayati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
S.aureus infection was found to be around 5%-35% and cases of S.aureus resistance increased by 22.8% due to people being less compliant in treatment. One of the preventions of resistance is to return to the use of natural materials, especially plants that have been scientifically and empirically proven, one of which is Mahkota Dewa Fruit (Phaleria macrocarpa) and Green Meniran Herb (Phyllanthus niruri L.). The study was conducted using the True Experimental method using S.aureus bacteria. 3 treatment groups were used, namely positive control (Amoxicillin), negative control (DMSO), as well as Mahkota Dewa extract (Phaleria macrocarpa) and Green Meniran Extract (Phyllanthus niruri L.). Using the disc diffusion method and the dilution method to determine the magnitude of the inhibition zone, the value of MIC, and MBC. The extract of the Crown of God Fruit, The Green Meniran Herb, as well as the combination of the two extracts have successive bacterial inhibitory power with an average of 18.02 mm; 15.95 mm; and 15.09 mm against S.aureus. Testing by the dilution method obtained a KHM value of 60% (0.06g/mL) in each extract. KBM is not obtained in each extract.